E-government in Canada : transformation for the digital age - Roy, Jeffrey (Governance series (Ottawa, Ont.), 2006)
"The rapid expansion of the Internet has fueled the emergence of electronic government at all levels in Canada. E-government's first decade featured online service underpinned by a technically secure infrastructure. This service-security nexus entails internal governance reforms aimed at realizing more customer-centric delivery via integration and coordination across departments and agencies. Yet, as online networking has become more pervasive and public demands for participation rise, pressures for greater openness and accountability intensify. The result is widening experimentation with online democracy. The e-governance focus is thus shifting toward issues of transparency and trust - and new possibilities for re-conceptualizing how power is organized and deployed. In sum, the prospects for digital transformation involve the interplay of these four dimensions: service, security, transparency and trust." "This book identifies the main drivers of e-government, assesses the responses of Canada's public sector to date, and sketches out the major challenges and choices that lie ahead. The findings will be of interest to those studying or working in the world of public sector management and e-governance. Book jacket."--Jacket